Efficacy of group cognitive behavioral therapy on depression among Muslim parents of autistic children in Jordan - Al Horany, Ahmed; Hassan, Siti Aishah; Baba, Maznah; Juhari, Rumaya (American - Eurasian Network for Scientific Information, 2011)
Parents with autistic children usually are advised to reduce depression in order to improve their mental health. However, studies on depression among parents of autistic children in Jordan are limited. Therefore, this study aimed to examine the effect of group Cognitive Behavior Therapy (CBT) among parents of autistics children in Jordan. An announcement was made for a group cognitive behavioral therapy at three special needs centers in Irbid- Jordan and BDI-II was administrated to 87 parents. Accordingly, 60 parents with the lowest test score were randomly assigned into experimental and control groups. Participants were tested in three times with the same scales, pre-test, post-test and follow up. Employing SPSS version 19 and repeated measures ANOVA, the three times scores of the experimental and control groups were compared. Result indicated that the participants have reduced their depression across time (T1, T2 and T3). Result showed that 50% of the variability in the depression within the participants may be due to the group counselling treatment. These findings are shown that there is significant difference at all times. These implied that the treatment had a strong lasting effect after one month of group counselling treatment. Moreover, results of this study also indicated that significant difference was found between the experimental and control groups (p < .001, ɳp2 = .56). This indicated that, experimental group is better than the control group in term of Depression by 56%. In conclusion, this study implied that group cognitive behaviour therapy is an effective treatment for depression among parents of autistic children.